The Naturalness and Accuracy of English Short Story Translation Into Indonesian - Safei, Nuh Hasanah; Salija, Kisman (ELT Worldwide: Journal of English Language Teaching, 2018)
The objectives of this research were to find out the naturalness of English short story translation into Indonesian and to find out the accuracy of English short story translation into Indonesian. This research employed descriptive qualitative research design which conducted at the second year students ofÂ  MTsN 1 Makassar in academic years 2017/2018 . The researcher used purposive sampling technique by taking one class from the twelve classes. The researcher chooses class VIII-11 which consisted of 40 students. The data were collected using document by translation text and interview. The results showed that the naturalness and accuracy of studentsâ€™ translation of short story entitled The Proud Lion gained score 7-8 with classification â€œalmost completely successfulâ€ from 30 students. And 10 students gained score 5-6 with classification â€œadequateâ€. It was caused by wrong choice of words and they were still less in selecting the indicated meaning so that their translation sound strange, unnatural, inaccuracy for the readers.